Spina bifida and anencephaly in Scotland. Issue 6453 (3rd November 1984) - Carstairs, V; Cole, S
Abstract : Data obtained from routine sources showed that from 1971 to 1982 the birth prevalences of spina bifida and anencephaly in Scotland fell. When known terminations after routine alpha fetoprotein screening were added to total births the adjusted birth prevalence could be calculated. In 1974-82 this fell by 40% for spina bifida (3 X 0-1 X 8) and 36% for anencephaly (2 X 2-1 X 4). These findings were compared with data on birth prevalences in England and Wales, Northern Ireland, and Glasgow. The fall in birth prevalences of spina bifida and anencephaly over the past decade appears to have been due both to a true fall in incidence as well as to increased screening and termination for these conditions.